Analysis of Exits in Fire Evacuation and Crowd Management in Multi-Functional Sports Halls (International Journal of Built Environment and Sustainability, 2025)
Crowd management and fire evacuation for assembly buildings are complex design processes in terms of design and construction. It should be designed as the main purpose of the safety of life and property to route the crowd to the nearest exit without creating congestion. This study aims to investigate the effect of exits in sports halls, which can respond to different functions from assembly buildings, for fire evacuation, and crowd management. In evacuation analyses, the effects of existing and alternative exits on the total evacuation time are investigated through Pathfinder evacuation simulations. For this purpose, a typical college sports hall was considered and possible exits were evaluated. Single and double blocking of exits in scenarios that may occur at different points were examined and total evacuation times were analyzed. In the study, it was found that spectators create congestion in sports halls (density of more than 3 people/m2) and are decisive in total evacuation time. It was determined that an exit at a distance from the spectator area could not provide an effective evacuation. Exits close to the spectator area were found to be effective in reducing the total evacuation time and could reduce the total evacuation time by 30 seconds. In conclusion, it is emphasized that the number of exits and exit locations in multi-functional sports halls should be made with rational and performance-based analysis. The importance of preventing congestion and positioning the exits to direct the crowd in an effective fire evacuation and crowd management is explained.
Keywords: Fire evacuation, Crowd management, Evacuation design, Evacuation simulation, Multi-functional sports halls.